Evaluation of in situ creep properties of frozen soils with the pressuremeter - Ladanyi, B.; Johnston, G. H. (National Academy of Sciences, 1973)
A series of field tests was carried out at a permafrost site near Thompson, Manitoba, to investigate the suitability of the Ménard Pressuremeter as a tool for in-situ determination of the rheological properites of frozen soils. Both short- term and long-term tests were conducted using the standard pressuremeter equipment with only minor modifications. Special care was taken in drilling and preparing the borehole for the tests to minimize the temperature disturbance. By using a newly developed method described in the paper, it was possible to obtain from the tests both the short-term and the long-term strength parameters. The first were obtained from conventional type pressuremeter tests, while the latter resulted from stage-loaded creep tests. In addition to the time dependent strength, the constitutive creep equation of the frozen soil was also established from the pressuremeter creep tests. The pressuremeter technique was found to be quite promising for creep testing of frozen soils. Its main advantages over laboratory methods used for similar purpose is that it is quicker, less expensive and involves a relatively large volume of soil. Its drawback is that it furnishes information on the soil behavior in only one direction, i.e., normal to the axis of the borehole which may be insufficient for foundation design if the permafrost stratum is anisotropic and contains horizontal ice lenses and layers. Afin de pouvoir évaluer les possiblités d'utilisation du pressiomètre Ménard pour la détermination sur place des propriétés rhéologiques des sols gelés, on a effectué une série d'essais pressiométriques dans le pergélisol près de la ville de Thompson au Manitoba. Ces essais, tant à court-terme qu'à long-terme, furent effectués en utilisant l'équipement standard avec seulement quelques modifications mineures. Le forage du trou, et sa préparation pour les essais, a été fait avec un grand soin pour éviter de déranger excessivement l'équilibre thermique du sol. Les résultats d'essais furent analysés par une nouvelle ...